Systemic delivery of mRNA and DNA to the lung using polymer-lipid nanoparticles. (August 2021) - Kaczmarek, James C.; Patel, Asha Kumari; Rhym, Luke H.; Palmiero, Umberto Capasso; Bhat, Balkrishen; Heartlein, Michael W.; DeRosa, Frank; Anderson, Daniel G.
Abstract: Non-viral vectors offer the potential to deliver nucleic acids including mRNA and DNA into cells in vivo . However, designing materials that effectively deliver to target organs and then to desired compartments within the cell remains a challenge. Here we develop polymeric materials that can be optimized for either DNA transcription in the nucleus or mRNA translation in the cytosol. We synthesized poly(beta amino ester) terpolymers (PBAEs) with modular changes to monomer chemistry to investigate influence on nucleic acid delivery. We identified two PBAEs with a single monomer change as being effective for either DNA (D-90-C12-103) or mRNA (DD-90-C12-103) delivery to lung endothelium following intravenous injection in mice. Physical properties such as particle size or charge did not account for the difference in transfection efficacy. However, endosome co-localization studies revealed that D-90-C12-103 nanoparticles resided in late endosomes to a greater extent than DD-90-C12-103. We compared luciferase expression in vivo and observed that, even with nucleic acid optimized vectors, peak luminescence using mRNA was two orders of magnitude greater than pDNA in the lungs of mice following systemic delivery. This study indicates that different nucleic acids require tailored delivery vectors, and further support the potential of PBAEs as intracellular delivery materials.